Overground, Body Weight Supported Gait Training Robots: A Scoping Review - Jaime Ramos-Rojas; Emma Perez-Martin; Antonio J. Del-Ama (IEEE Access)
Gait rehabilitation is essential for improving mobility in patients with neurological impairments. Yet, conventional and treadmill-based robotic devices often fail to replicate natural walking conditions, which has been identified as one of the main drawbacks to achieving clinical efficacy. The scientific community is figuring out that a new generation of robotic devices is needed to enable impaired users to ambulate independently, navigate real-world environmental barriers, and maintain and train postural stability during walking. Unlike previous reviews, which focus on either standalone exoskeletons or treadmill-based rehabilitation systems, this review aims to analyze robotic devices for over-ground body-weight-supported gait training with lower limb guidance, filling a gap in a field that has not been systematically reviewed. From 240 screened articles, 15 different robotic devices were identified. Most devices combine exoskeleton-based lower-limb assistance, body-weight support (BWS), and mobile frame, aiming to facilitate ambulatory gait training while assisting leg motion in the sagittal plane. All devices featured assistance based on predefined joint kinematics. Only six devices have undergone clinical feasibility studies with their target population. Yet, despite the potential of this type of device, no randomized controlled trials have been conducted to investigate therapeutic efficacy. Future work should focus on addressing synchronization, and mechanical complexity issues through adaptive and real-time control strategies and the integration of sensor systems to improve and facilitate daily rehabilitation performance, and prioritize enabling robotic-assisted functional exercises, such as weight-bearing and dynamic balance tasks, to maximize rehabilitation outcomes. Furthermore, adequately designed clinical evaluations through large-scale, multi-center randomized controlled trials should also be conducted to ensure both the feasibility and effectiveness of this type of rehabilitation device.